2011
DOI: 10.1182/blood-2010-03-273011
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 deficiency compromises mouse embryonic stem cell hematopoietic differentiation, and embryonic and adult hematopoiesis in the mouse

Abstract: SIRT1 is a founding member of a sirtuin family of 7 proteins and histone deacetylases. It is involved in cellular resistance to stress, metabolism, differentiation, aging, and tumor suppression. SIRT1 ؊/؊ mice demonstrate embryonic and postnatal development defects. We examined hematopoietic and endothelial cell differentiation of SIRT1 ؊/؊ mouse embryonic stem cells (ESCs) in vitro, and hematopoietic progenitors in SIRT1 ؉/؉ , ؉/؊ , and ؊/؊ mice. SIRT1 ؊/؊ ESCs formed fewer mature blast cell colonies. Replate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 50 publications
8
90
1
Order By: Relevance
“…SirT1 has been reported to be involved in a variety of cellular functions. 35 Recent data also suggests that SirT1 is a critical mediator in regulation of various development genes during stem cell differentiation 36 and has an important role in various cellular differentiations, including endothelial progenitor cells, 37 hematopoietic cells 38 and osteoblasts. 39 Traditionally, SirT1 has mainly been linked to gene repression; 40 however, accumulating evidence also strongly suggests that SirT1 can act both positively and negatively to control gene expression by recruiting a different set of coactivators and corepressors 41 or via a transcriptional mechanism.…”
Section: S Ir T 1 a C T A 2 T A G Lnmentioning
confidence: 99%
“…SirT1 has been reported to be involved in a variety of cellular functions. 35 Recent data also suggests that SirT1 is a critical mediator in regulation of various development genes during stem cell differentiation 36 and has an important role in various cellular differentiations, including endothelial progenitor cells, 37 hematopoietic cells 38 and osteoblasts. 39 Traditionally, SirT1 has mainly been linked to gene repression; 40 however, accumulating evidence also strongly suggests that SirT1 can act both positively and negatively to control gene expression by recruiting a different set of coactivators and corepressors 41 or via a transcriptional mechanism.…”
Section: S Ir T 1 a C T A 2 T A G Lnmentioning
confidence: 99%
“…However, loss of Sirt1 confers a growth advantage in culture to HSCs under conditions of nutrient limitation (Narala et al, 2008), suggesting that SIRT1 negatively regulates HSC self-renewal under some conditions. In a different mouse model for Sirt1 constitutive deletion, SIRT1 promotes HSC self-renewal in low oxygen when assessed at early ages (Ou et al, 2010). Defects in HSC self-renewal under both basal and low oxygen conditions are exacerbated in older mice compared with young adults (Ou et al, 2010).…”
Section: Histone Acetylation In Aging Stem Cellsmentioning
confidence: 99%
“…In a different mouse model for Sirt1 constitutive deletion, SIRT1 promotes HSC self-renewal in low oxygen when assessed at early ages (Ou et al, 2010). Defects in HSC self-renewal under both basal and low oxygen conditions are exacerbated in older mice compared with young adults (Ou et al, 2010). The role of SIRT1 in adult NSCs has not yet been characterized, but SIRT1 plays a role in directing cell fate decisions of embryonic neural progenitors in response to different extracellular conditions (Hisahara et al, 2008;Prozorovski et al, 2008).…”
Section: Histone Acetylation In Aging Stem Cellsmentioning
confidence: 99%
“…Consistent with these concerns, a recent study showed that SIRT1 deficiency leads to impaired mouse embryonic stem cell (mESC) differentiation into hematopoietic progeny in vitro, indicating a possible role for SIRT1 in the development of primitive hematopoiesis in mouse embryos. 16 Several SIRT1 knockout models have been established using different targeting strategies in various genetic backgrounds, with the common feature of almost universal embryonic or perinatal mortality in the inbred 129SV background but a significant fraction of mice surviving to adulthood in other genetic backgrounds. [11][12][13][14] Specifically, the deletion of SIRT1 exon 4 in the C57BL/6 background allowed some of the mice to survive to weaning while conferring the same gross phenotype of SIRT1 deletion.…”
Section: Introductionmentioning
confidence: 99%